Growing Tolerance Through Active Learning Methods In Generation Z Students at Elementary School X Surabaya - Anastasia Paramita; Suryanto Suryanto (Universitas PGRI Adi Buana Surabaya, 2021)
This study illustrates (1) the forms of intolerance that frequently occur between generation Z’s primary school students, (2) factors that lead to the occurrence of intolerance, and (3) the role of school in developing students’ tolerance characteristics through active learning methods in Generation Z of Primary School students. This study uses a qualitative approach with descriptive study case method. Data collection using semi-structured interview method. Data analysis techniques use thematic analysis. The outcome of this study shows that active learning models, especially through collaborative learning activities that are regularly carried out, will increase the frequency of student encounters so that they can get to know their friends' characters better. Besides that, daily reflection writing activity also gave students the opportunity to explore the strengths and weaknesses of daily behavior of themselves, therefore allowing students to have a reflective process to improve their attitudes and behaviors that are less favorable to their friends' environment. Hopefully, all schools can develop and maximize active learning techniques to be able to provide a deeper understanding of tolerance behavior.